2007
DOI: 10.1080/09595230701373966
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacists on the front line in providing support for nicotine replacement therapy and bupropion purchasers

Abstract: Pharmacists report providing a sizeable amount of advice to purchasers of NRT and bupropion. Recommendations for enhancing the role of pharmacists in influencing the use of cessation pharmacotherapies are discussed briefly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Moreover, community pharmacists are uniquely positioned to simultaneously provide both smoking cessation services and NRT to smokers who want to quit [15]. There is also evidence that pharmacists do see themselves as playing a role in providing cessation support to their clients [13,[16][17][18][19][20][21]. Increasing the utilization of pharmacists in smoking cessation activities may have a positive impact on reducing smoking rates at the population level.…”
mentioning
confidence: 99%
“…Moreover, community pharmacists are uniquely positioned to simultaneously provide both smoking cessation services and NRT to smokers who want to quit [15]. There is also evidence that pharmacists do see themselves as playing a role in providing cessation support to their clients [13,[16][17][18][19][20][21]. Increasing the utilization of pharmacists in smoking cessation activities may have a positive impact on reducing smoking rates at the population level.…”
mentioning
confidence: 99%
“…Three reasons for the barriers to development of the pharmacist's professional actions may be identified in the literature under analysis: (1) The pharmacist and the pharmaceutical occupation, for instance, the pharmacist's lack of knowledge on drugs and their uses (Paul et al, 2007) or on oral health (Dickinson, Howlett, Bulman, 1995;Maunder, Landes, 2005), conflict of roles in the community pharmacy due to the need to sell goods (LloydWilliams, 2003), lack of skills and specific training for actions in health promotion, and therefore qualification and training programs for pharmacists are needed (O'Loughlin et al, 1999; Vinholes, Alano, Galato, 2009); furthermore, personal impairments such as fear, resistance to new concepts and lack of self-reliance, the characteristics that have been largely referred to in the case of pharmacists (Boyle, Coffey, Palmer, 2004;Sunderland et al, 2006). (2) The pharmacy and work organization, such as lack of proper remuneration, extensive actions to be accomplished (Aquilino et al, 2003;George et al, 2010) and the consequent lack of time (Patwardhan, Chewning, 2009), lack of proper instruments for the required actions (O'Loughlin et al, 1999), communication and role conflicts, lack of physical space and privacy for patient advice (Foster, Smith, 1998;O'Loughlin et al, 1999;Nichols-English, Poirier, 2000).…”
Section: Barriers To the Development Of Practices In Health Promotionmentioning
confidence: 99%
“…But when smokers access drugs in real-world circumstances, they are most likely to receive no support or advice (for example, when buying NRT from a supermarket) or only brief, sometimes perfunctory advice when a healthcare provider or pharmacist is too busy to spend much time with a customer. A NSW survey of 700 pharmacies (Paul, Tzelepis et al 2007) reported that pharmacists claimed to spend an average of five minutes discussing stop smoking medications with smokers, which means that many would spend less time than that.…”
Section: Randomised Controlled Trialsmentioning
confidence: 99%